Facts about Calcium - Linda B. Bobroff (EDIS)
Revised! FCS-8703, a 3-page fact sheet by Linda B. Bobroff, answers common questions about calcium. Includes links to additional information. Published by the UF Department of Family Youth and Community Sciences, December 2008.